# Most Important Reasoning Quiz for IBPS RRB Exams

## Most Important Reasoning Quiz for IBPS RRB Exams

DIRECTIONS (Q. 1-5): Answer these questions referring to the symbol-letter-number sequence given below:
A  0  I  ?  E  G  4  B  H  7  5  @  K  8  D  N  £  Q  Z  \$  W  3  C  1  9  *  l  B  2  S  6 %
1. How many such consonants are there in the above sequence which are immediately preceded by a symbol and immediately followed by a digit ?
1)  One
2)  Two
3)  None
4)  Three
5) More than three
2. What should come in place of the question mark (?) in the following sequence ?
AIG,  4H@,   KDQ,   ?,   ILS
1)  ZW1
2)  NQ\$
3) @8N
4)  \$W9
5) None of these
3. Which of the following is exactly in the midway between the ninth from left end and the sixth from right end ?
1) Q
2)  Z
3) £
4)  W
5)  None of these
4. If the first sixteen elements are written in the reverse order then which of the following will be seventh to the left of twelfth element from right end ?
1) 7
2) I
3) G
4) K
5) None of these
5. How many such symbols are there in the above sequence which are immediately preceded as well as followed by consonant?
1) None
2) One
3) Two
4) Three
5) None of these
Directions (Q. 6-8): In the questions given below, relationship between different elements is shown in the statements. These statements are followed by four conclusions. You have to decide which conclusion definitely follows from the statement.
6. Statements: P < Q, R > T, W ≥ X, Q ≥  W, X = R
Conclusions:
I. P < Q
II. Q ≥  R
III.T > W
IV.W > P
1) Only I and IV
2) Only I and II
3) Only III and IV
4) Only II
5) Only I
7. Statements: A ≥  B, E ≥  F, D = E, B ≥  C, C ≥  D
Conclusions:
I. F > D
II. C ≥  E
III.F ≤ A
IV. E ≤ B
1) Only I and IV
2) Only II and III
3) Only III and IV
4) Only II and IV
5) None of these
8. Statements: P ≥  C, Q  ≥  G, F  ≥  M, M < G, C > F
Conclusions:
I. M < P
II. Q > M
III.P > Q
IV.M = G
1) Only I and II
2) Only II and III
3) Only III and IV
4) Only I and IV
5) None of these
Directions (Q. 9-13) : In every questions two rows are given and to find out the resultant of a particular row you need to follow the following rules :
Step 1: If an odd number is followed by an even number then the resultant comes by multiplying the numbers.
Step 2: If an even number is followed by an odd (non prime) number then the resultant will be the subtraction of the odd number form the even number.
Step 3: If an even is followed by prime number (except 2) then the resultant will be the addition of both the numbers.
Step 4: If an odd number is followed by a perfect cube then the resultant will be the subtraction of the cube root of that number from the odd number.
Step 5: If odd number is followed by another odd number the resultant will be the addition of both the numbers.
9. Find the sum of the resultant of two rows. If P is the resultant of first row.
11      64         4
P        7         2
1) 72
2) 43
3) 70
4) Can’t be determined
5) None of these
10. Find the difference between the resultant of first and second row.
11      6           21
31      1000    13
1) 11
2) 13
3) 9
4) 22
5) None of these
11. If the sum of the resultants of two rows is 38. Then find the value of M.
36      33     4
16       7      M
1) 8
2) 6
3) 1
4) 3
5) None of these
12. Find the sum of two rows.
8         11       4
26      21      5
1) 128
2) 86
3) 66
4) 80
5) 96
13. Find the resultant of first row if X is the resultant of second row ?
15    X      6
8      31    25
1) 68
2) 36
3) 66
4) 18
5) None of these

1. 2; @K8,  \$W3
2. 1; ZW1
3. 1
4. 2
5. 3; N£Q,    Z\$W
6. 4; P < Q, Q ≥ W, W ≥ X, X = R, R > T
7. 5; A ≥ B, B ≥ C, C ≥ D, D = E, E ≥ F
8. 1; P ≥ C, C > F, F ≥ M, M < G, G ≤ Q
9. 3
• R1 = 11    64    4
• = (11–4)    4    (Rule – 4)
• = 7     4
• = (7 × 4) (Rule – 1)
• = 28
• R2 = P     7     2
• = 28    7   2
• = (28 + 7)   2     (Rule – 3)
• = 35    2
• = 35 × 2    (Rule – 1)
• = 70
10. 1
• R1 = 11     6    21
• = (11 × 6)    21    (Rule – 1)
• = 66     21
• = (66 – 21)         (Rule – 2)
• = 45
• R2 = 31    1000     13
• = (31 – 10)     13    (Rule – 4)
• = 21    13
• = (21 + 13)         (Rule – 5)
• = 34
•  Required difference = 45 – 34 = 11
• 11. 4;
• R1 = 36     33     4
• = (36 – 33)    4     (Rule – 2)
• = 3     4
• = (3 × 4)         (Rule – 1)
• = 12
• Resultant of second number = 38 – 12 = 26
• R2 = 16    7    M =  26
•  = (16 + 7)    M  = 26      (Rule – 3)
• = 23     M = 26
• Here the value of M should be 3 (follow rule – 5) and final value = 26 – 23 = 3
• 12. 2;
• R1 = 8    11    4
• = (8 + 11)     4     (Rule – 3)
• = 19      4
• = (19 × 4)        (Rule – 1)
• = 76
• R2 = 26     21     5
• = (26 – 21)      5       (Rule – 2)
• = 5      5
• = (5 + 5)          (Rule – 5)
• = 10
• Required sum = 76 + 10 = 86
• 13. 3;

###### Share To: 